Oxygen Glucose Deprivation Induced Prosurvival Autophagy Is Insufficient to Rescue Endothelial Function - Natarajan, Venkateswaran; Mah, Tania; Peishi, Chen; Tan, Shu Yi; Chawla, Ritu; Arumugam, Thiruma Valavan; Ramasamy, Adaikalavan; Mallilankaraman, Karthik (Frontiers in Physiology, 2020)
Endothelial dysfunction, referring to a disturbance in the vascular homeostasis, has been implicated in many disease conditions including ischemic/reperfusion injury and atherosclerosis. Endothelial mitochondria have been increasingly recognized as a regulator of calcium homeostasis which has implications in the execution of diverse cellular events and energy production. The mitochondrial calcium uniporter complex through which calcium enters the mitochondria is composed of several proteins, including the pore-forming subunit MCU and its regulators MCUR1, MICU1 and MICU2. Mitochondrial calcium overload leads to opening of MPTP (mitochondrial permeability transition pore) and results in apoptotic cell death. Whereas, blockage of calcium entry into the mitochondria results in reduced ATP production thereby activates AMPK-mediated pro-survival autophagy. Here, we investigated the expression of mitochondrial calcium uniporter complex components (MCU, MCUR1, MICU1 and MUC2), induction of autophagy and apoptotic cell death in endothelial cells in response to oxygen-glucose deprivation. Human pulmonary microvascular endothelial cells (HPMVECs) were subjected to oxygen-glucose deprivation (OGD) at three-hour timepoints up to 12 hours. Interestingly, except MCUR1 which was significantly downregulated, all other components of the uniporter (MCU, MICU1, MICU2) remained unchanged. MCUR1 downregulation has been shown to activate AMPK mediated pro-survival autophagy. Similarly, MCUR1 downregulation in response to OGD resulted in AMPK phosphorylation and LC3 processing indicating the activation of pro-survival autophagy. Despite the activation of autophagy, OGD induced Caspase-mediated apoptotic cell death. Blockade of autophagy did not reduce OGD-induced apoptotic cell death whereas serum starvation conferred enough cellular and functional protection. In conclusion, the autophagic flux induced by MCUR1 downregulation in response to OGD is insufficient in protecting endothelial cells from undergoing apoptotic cell death and requires enhancement of autophagic flux by additional means such as serum starvation.